In Memoriam - Thee Kian Wie : Dedicated Scholar and Public Intellectual - Hill, Hal (Taylor and Francis, 2014)
With the passing of Thee Kian Wie (hereafter ‘Kian Wie’) on February 8, 2014, aged 79 years, Indonesia lost one of its most distinguished citizens. Kian Wie, or ‘Pak Thee’ as he was widely known to Indonesians, was a dedicated and productive scholar, a public intellectual, a life-long civil servant, a mentor, a raconteur, and a cosmopolitan able to converse with ease in several languages. He had a remarkable empathy with people across nationalities, ethnicities and socioeconomic classes. His circle of friends and colleagues at home and abroad was extraordinarily wide. In fact, it is difficult to think of any other Indonesian academic social scientist of his generation with a wider international network; he was a bridge between the Indonesian and international scholarly communities. And above all else, he was a warm, charming, generous, principled and modest human being, with a fierce sense of justice and support for the less privileged.